Mechanical performance and biocompatibility study of methacrylated Gellan gum hydrogels with potential for nucleus pulposus regeneration - Silva-Correia, Joana (2012)
Methacrylated gellan gum hydrogels, obtained either by ionic- (iGGMA) and photo-crosslinking (phGG-MA), have been investigated as potential biomaterials for supporting nucleus pulposus (NP) regeneration and/or repair [1,2]. In previous work, some advantages were attributed to GG-MA hydrogels, such as: (i) the possibility to control endothelial cells infiltration and blood vessel ingrowth’s, (ii) tunable and improved mechanical properties, and (iii) in situ gelation, within seconds to few minutes. In this study, the mechanical and biological performance of these hydrogels was firstly evaluated in vitro. Human intervertebral disc (hIVD) cells obtained from herniated patients were cultured within both hydrogels, for 1 up to 21 days. Dynamic mechanical analysis and biological characterization (calcein-AM staining, ATP and DNA quantification and PCR) were performed after specific times of culturing. A biocompatibility study was also performed in vivo, by subcutaneous implantation of acellular iGG-MA and phGG-MA hydrogels in Lewis rats for the period of 10 and 18 days. Tissue response to the hydrogels implantation was determined by histological analysis (haematoxylin-eosin staining). The in vitro study showed that both cell loading and culturing time do not have an effect on the mechanical properties of the hydrogels. Regarding their biological performance, the iGG-MA and phGG-MA hydrogels showed to be effective on supporting hIVD cells encapsulation and viability up to 21 days of culturing. Human IVD cells were homogeneously distributed within the hydrogels and maintained its round-shape morphology during culturing time. The in vivo biocompatibility study showed that iGG-MA and phGG-MA hydrogels do not elicit any deleterious effect, as denoted by the absence of necrosis and calcification, or acute inflammatory reaction. A thin fibrous capsule was observed around the implanted hydrogels. The results presented in this study indicate that the iGG-MA and phGG-MA hydrogels are stable in vitro and in vivo, support hIVD cells encapsulation and viability, and were found to be well-tolerated and non-cytotoxic in vivo, thus being potential candidates for NP regeneration.